1974
DOI: 10.2134/agronj1974.00021962006600010004x
|View full text |Cite
|
Sign up to set email alerts
|

Weanling Meadow Vole Responses to Crownvetch Forage1

Abstract: Crownvetch (Coronilla varia L.) has been reported to contain antiquality constituents. Feeding trials were conducted to determine the feasibility of using the weanling meadow vole (Microtus pennsylvanicus) as a bioassay to assess the effects of these antiquality constituents on feed intake, body‐weight change, and ration digestibility. The feeding value of crownvetch forage was compared with that of alfalfa (Medicago sativa L.), birdsfoot trefoil (Lotus corniculatus L.), and sainfoin (Onobrychis viciaefolia Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

1976
1976
2002
2002

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 4 publications
1
14
1
Order By: Relevance
“…Regression of feed intake against level of COLM in the diet yielded the equation: Y (feed intake) = 3.98-0.013x (r =-0.97; PO.01) where x is the level of COLM in the diet. The results obtained in this study with respect to feed intake is in agreement with that of phenolic-related studies by Barnes et al (1974), Shenk et al (1974) and Jung and Fahey (1983). Chemical analyses of the leaves of Chromolaena odorata in the present study and that of Apori et al (2000) indicate that it contains tannins.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Regression of feed intake against level of COLM in the diet yielded the equation: Y (feed intake) = 3.98-0.013x (r =-0.97; PO.01) where x is the level of COLM in the diet. The results obtained in this study with respect to feed intake is in agreement with that of phenolic-related studies by Barnes et al (1974), Shenk et al (1974) and Jung and Fahey (1983). Chemical analyses of the leaves of Chromolaena odorata in the present study and that of Apori et al (2000) indicate that it contains tannins.…”
Section: Resultssupporting
confidence: 91%
“…Phenolic compounds, including tannins, reportedly affect feed intake because of unpalatability. A study by Shenk et al (1974) indicated that meadow voles ingested less feed with as little as 15% phenolic-containing crownvetch in the diet. Prior extraction of crownvetch with ethanol removed the factor responsible for reduced intake by voles .…”
Section: Resultsmentioning
confidence: 99%
“…Despite previous reports that crownvetch was toxic to meadow voles in caged feeding studies (Lewis et al, 1983;Shenck et al, 1974), we observed foraging on crownvetch leaves (but not stems) by voles in this GMS. The densely matted crownvetch also supported substantial vole populations, and its long procumbent stems provided bridges for voles to climb over and inside the mesh guards, gaining access to feed on tree trunks.…”
Section: Resultscontrasting
confidence: 99%
“…Voles adequately sample local habitats because they consume a variety of vegetation equivalent to one third of their body weight each day. Moreover, the vole is used as a model herbivore (Sh76;Sh75;Sh74). The abundance of voles enables one to destructively sample thyroid glands relatively easily and at little expense.…”
Section: Resultsmentioning
confidence: 99%
“…is used extensively as a model organism for studying population dynamics (Kr74), nutrition (Ke78; Sh76;Sh75;Barn74,Br74;Sh74;Sh70), and bioaccumulation (Wi78; Ge77) because of its position in the terrestrial food chain, widespread distribution, abundance, small size, and limited home range (Am69; Va69). These attributes also make the vole a good model for studies involving radionuclide pollution.…”
Section: Introductionmentioning
confidence: 99%